EFFECTIVENESS OF ORGANIC VEGETABLE PLANTING PRODUCTIVITY WITH HYDROPONIC AND VERTICULTURE METHODS AT SMA CENDRAWASIH II SOUTH TANGERANG CITY - Munawir, Abdillah; Rusdiyanto, Edi; Muna, Siti Umamah Naili (LPPM Univ. Ibn Khaldun Bogor, 2024)
The implementation of service at Cendrawasih II High School focuses on the organic vegetable planting system with hydroponic and verticulture methods. The method used is Participatory Learning through Participatory teachers and school partner students with discussion, practice and demonstration materials. The results of the dedication explain the hydroponic method system, a plant technique that is grown in a nutrient solution consisting of a mixture of water and all the essential nutrients needed by plants for optimal growth. For the verticulture method system, a farming technique in which plants are planted vertically in multilevel containers or multilevel structures. Growing vegetables in verticulture can be a good solution to make efficient use of space, but its success depends on good planning, consistent care, and proper selection of plants. Verticulture farming method, yields are quite good because the multilevel system allows cultivation in limited space, maximizing vertical land use. Hydroponic systems, yields are impressive due to the simple system and excellent control of nutrients provided to plants with higher organic vegetable productivity and grow faster than verticulture systems.